Vous êtes sur la page 1sur 7

a

e z V z

V = 0

V z d 2 V

= 0 d z 2 + V 1 a e z a
= 0
d
z 2
+ V 1
a
e z
a

V (z ) = Az + B V (0) = V 1 V (a ) = V 2 V (z ) = V 2 V 1 z

E = gradV = d V

2 − V 1 z E = − grad V = − d V d z

d

z

e z E = V 2 V 1

Oz E

− d V d z e z E = − V 2 − V 1 Oz

e z

e z E z E = E (z )e z

E

Oz Σ

0 < z 1 < a a < z 2

e z E Oz Σ 0 < z 1 < a a < z 2 E.

E.dS = Q int Σ E (z 1 ) =

ε

0

QΣ

0

Q E (z ) = 0 0 < z < a Sε
Q
E (z ) =
0 0 < z < a

Q

Q

Q

Sε 0 C = Sε 0 a
0
C = Sε 0
a

=

V 2 V 1

a

C = Q V 2

V 1

O V

r

r O

O

d r r 2 d V

1

r 2 d

d

r

= 0

V (r ) = A + B V (R 1 ) = V 1 V (R 2 ) = V 2 V (r ) = R 1 R

r

R 2

R 1 (V 1 V 2 ) 1

2

r + V 1 R 1 V 2 R 2 R 1 R 2

E = gradV E (r ) =

R 1 R R 2

R 1 (V 1 V 2 )

2

1

r 2

O

O E = E (r )e r

R 1 < r < R 2 4 πr 2 E (r ) = Q

ε

0

Q

4πr C ′ = Q V 2 = 4 πε 0 V 1 − R
4πr
C ′ =
Q V 2 = 4 πε 0
V 1 −
R 1 R 2
R 2 − R 1

E (r ) =

2 ε 0

R 1 R R 2

R 1 (V 1 V 2 )

2

1

r 2 =

Q

4πr 2 ε 0

R 2 R 1 R R 1 R 2 R 2 4 πR 2

a
a

a = R 2 R 1 C = 0

P = ui

R 2 4 πR 2 a a = R 2 − R 1 C ′ =

δW e = ui dt δW e = V 0 dq

dU = δQ + δW e = δQ + V 0 dq δQ =

d U = δQ + δW e = δQ + V 0 d q δQ =

dU V 0 dq dS δQ δQ T dS dU V 0 dq T dS

T

dG dG = dU T dS S dT q dV 0 V 0 dq

V 0 dG = dU T dS V 0 dq

G

dG = dU T dS q dV V dq

δQ = T dS dG = dU δQ q dV V dq = δW e q dV V dq

δW e = V dq dG = q dV q = CV dG = CV dV = C d V 2

2

G(V = 0) = 0 G(V 0 ) =

2 2 1 CV 0
2
2 1 CV
0

γ

j E j = γ E

j E = 0

2 2 1 CV 0 γ j E j = γ E j E = 0

div E = ρ 0 ρ E = 0

ǫ

ρ = 0

E E (x = 0 + ) E (x =

0 ) = σ 0 u x E (x = 0 ) = 0

− ) = σ 0 u x E ( x = 0 − ) = 0

ε

E (x = 0 + ) = σ 0 u x ε
E (x = 0 + ) = σ 0 u x
ε

= − ρ d x 2 ε 0
= − ρ
d
x 2
ε
0

V x d 2 V

ρ

= Ze n (Ze ) Ze n (Ze ) = Ze n 0 exp ZeV n 0 exp ZeV

kT

kT

ρ (x) = − 2 n 0 Ze sh ZeV ( x ) kT
ρ (x) = − 2 n 0 Ze sh ZeV ( x )
kT

d 2 V

= 2n 0 Ze sh ZeV ( x ) d x 2 ε 0 kT
= 2n 0 Ze
sh ZeV ( x )
d
x 2
ε 0
kT

V 0 kT

Ze

sh ZeV kT ( x )

ZeV ( x ) kT

d 2 V

d

x 2

2n 0 Ze

ZeV ( x )

ε

0

kT

=

V ( x )

ξ

2

V (x) = A exp x ξ

V (x) = V 0 exp − x ξ exp − x u x ξ
V (x) = V 0 exp − x
ξ
exp − x u x
ξ
ξ

V

(0) = V 0 V () = 0

E = d V u x E = V 0

V 0 V ( ∞ ) = 0 E = − d V u x E

d

x

+ B exp x

ξ

=

ξ

E (x = 0 + ) = σ 0 u x E (x = 0 + ) = V 0 u x V 0

0 u x E ( x = 0 + ) = V 0 u x V

ε

0 u x E ( x = 0 + ) = V 0 u x V

ξ

ξ

ε 0
ε
0

V 0 = σ ξ ξ

= σ

ε 0

n 0 = 0 ,01 ∗ N A Z = 1

ξ = 1 ,09 .10 8 m 0 ,0109 µm

kT = 25 ,9 mV 300 K

Ze

V 0 kT

Ze

ξ

E = d V

d 2 V

d E = d E

d

x

ε

V

d

0

d 2 V

d E = E d x 2 d V sh ZeV ( x ) E
d
E
= E
d
x 2
d V
sh ZeV ( x )
E dE = 2n 0 Ze
ε 0
kT

d x d x 2

=

d V d x

=

2n 0 Ze

E d E

d

V

sh ZeV ( x ) kT

dV

E

0

( x )

E dE =

0

V ( x )

2n 0 Ze

ε

0

sh ZeV ( x ) kT

dV E ( 2 x ) 2

2n 0 Ze kT

ε

0

Ze

=

ch ZeV ( x ) kT

E 2 = 8n 0 kT

ε

0

sh 2 ZeV ( x )

2kT

ε

0

sh ZeV 0

2kT

E = 8n 0 kT

sh ZeV ( x ) ε 2kT 0 σ = √ 8 n 0 kT
sh ZeV ( x )
ε
2kT
0
σ = √ 8 n 0 kT ε 0 sh ZeV 0
2kT
ε 0 = 1 ,42 .10 − 4 C · m − 2 σ
ε
0
= 1 ,42 .10 − 4 C · m − 2
σ

x = 0 E = σ

E = 8n 0 kT

1

V 0 kT

Ze

g

dG = q dV

V 0

0

σ (T,V )dV

dg = σ dV g (T,V 0 ) =

V

σ g (T,V 0 ) =

0

0

g (T,V 0 ) = 8 n 0 kT ε 0 2kT g (T,V 0 ) = 16 kT n 0 ξ sh ZeV 0

4kT
4kT
0 ) = − 16 kT n 0 ξ sh Z e V 0 4kT Ze

Ze ch ZeV 0

2kT

1 = 8 kT n 0

Ze 1 kT ε 0 2n 0

2 sh 2 ZeV 0

4kT

8 n 0 kT ε 0 sh ZeV dV

2kT

|eV 0 | ≪ kT g (T,V 0 ) ≈ − 16 kT n 0 ξ ZeV 0

4kT 2 = n 0 ξ ( ZeV 0 ) 2 kT

=

ε 0 V

0

ξ

( Ze) 2 2n 0 kT ε 0

2

2

g (T,V 0 ) ≈ − ε 0 V

2 0 2ξ
2
0

|eV 0 | ≪ kT V 0 σ

ξ

L = D 2 r

= 2n 0 Ze sh ZeV ( x ) d x 2 ε 0 kT
= 2n 0 Ze
sh ZeV ( x )
d
x 2
ε 0
kT

L r

d 2 V

Ox

x =

L

2
2

E = 0

E dE = 2n 0 Ze dV 0

ε 0

sh ZeV ( x ) kT

E

( x )

d E 2 2 =

V ( x )

V

m

2n 0 Ze

ε

0

sh ZeV ( x )

kT

dV E 2 2

2n 0 Ze kT

ε

0

Ze

=

ch ZeV ( x )

kT

ch ZeV m

kT

E 1 = 2 n 0 kT

ε 0

E 1 ch ZeV ( x ) − ch ZeV m E (x) = kT
E 1 ch ZeV ( x ) − ch ZeV m
E (x) =
kT
kT
E (x = 0 + )
= σ 0 σ = ε 0 E 1 ch ZeV 0 − ch ZeV m
ε
kT
kT

ξ B > 0 w R > 0

A > 0

κ O y → −∞ κ → ∞ y 0

B C y

B

A

= A

d

y

d

κ

= exp(κ )+

A 1

κ = 0 exp(κ max ) =

B

A B κ max y (κ max ) =

1

A

1 A

1

2

max

B

κ max

B κ

y (κ max ) = 0 κ max = 1

B A C = e − 1
B A C = e − 1

B C w < 0

B

A

> A

w L = 0

L 0 w

− 1 B C w < 0 B A > A w L = 0 L

a 2 = 4 R M

a = 2 √ 2 R M a = 407 pm
a = 2 √ 2 R M
a = 407 pm

4M

µ =

N

A

4M N A a 3
4M
N A a 3

µ = 10 ,6 .10 3 kg · m 3

r H 0 r S 0

4 Ag + O 2 = 2 Ag 2 O 2 Pb + O 2 = 2 PbO

r G 0 = ∆ r H 0 T r S 0

r G 0

r G 0 = ∆ r H 0 − T ∆ r S 0 ∆ r

T 1235 K r H 0 = 62 ,2 kJ · mol 1 r S 0 = 132 ,4 J · mol 1

r G 0 = 62 ,2 .10 3 + 132 ,4 T J · mol 1

1235 KT 1380 K r H 0 = 107 ,4 kJ · mol 1 r S 0 = 168 ,8 J · mol 1

r G 0 = 107 ,4 .10 3 + 168 ,8 T J · mol 1

T 588 K r H 0 = 438 ,2 kJ · mol 1 r S 0 = 201 ,6 J · mol 1

r G 0 = 438 ,2 .10 3 + 201 ,6 T J · mol 1

588 K T 1160 K r H 0 = 448 ,4 kJ · mol 1 r S 0 = 219 J · mol 1

r G 0 = 448 ,4 .10 3 + 219 T J · mol 1

1160 KT r H 0 = 425 kJ · mol 1 r S 0 = 198 ,8 J · mol 1

r G 0 = 425 .10 3 + 198 ,8 T J · mol 1

T K ∆ r G 0 kJ mol − 1 ∆ r G 0 kJ
T K
∆ r G 0 kJ mol − 1
∆ r G 0 kJ mol − 1
298
373
588
1160
1235
1380
− 22 ,7
101 ,3
1
− 378 ,1
− 319 ,7
− 194 ,3
125 ,5
− 150 ,7
2

P (O 2 ) = 0 ,2 bar

K 0 =

p

0

P (O 2 ) = 5 r G 0

1

=

RT ln K 0 T 1 = 427 K T < T 1

1 = − RT ln K 0 T 1 = 427 K T < T 1

T > T 1

Q = P (O 2 ) = 5

p

0

A = − ∆ r G 0 (T 2 ) − RT ln Q 2
A
= − ∆ r G 0 (T 2 )
− RT ln Q
2
A = 133 kJ · mol − 1

Ag + Cl

 
 
Cl −

Cl

Ag +

Ag +

a = 2 r (Cl ) + 2 r (Ag + ) r (Ag + ) = 97 ,5 pm

   

n = 1 ,20 .10 6

f G 0

E

RT

=

0

E

f H RT

+

r S

0

E

R

0

f H E > 0 T

d[Cu 2+ ( A )]

d t

d[Cu 2+ ( B )]

d t

d[Cu + ]

d t

= k 1 [Cu 2+ (A)] k 3 [Cu 2+ (A)]
= k 1 [Cu 2+ (A)] k 2 [Cu 2+ (B )]

= k 2 [Cu 2+ (B )] + k 3 [Cu 2+ (A)]

[Cu 2+ (A)] = A exp (k 1 + k 3 )t [Cu 2+ (B )] =

B exp k 2 t + A exp (k 1 + k 3 )t

[Cu 2+ ] tot = D exp k 2 t + D exp (k 1 + k 3 )t

d ln K

d

T

=

E A 2 K = K 0 exp

RT

E A
E
A

RT E A T

1

ln K T

1 ln K T E A (1+3) = 5 , 2 kJ · K − 1

E A (1+3) = 5 ,2 kJ · K 1 E A (2) = 3 ,5 kJ · K 1

E A 1 ≈ E A 3 = 5 ,2 kJ · K − 1
E A 1 ≈ E A 3 = 5 ,2 kJ · K − 1

s 1 300 K k 1 + k 3 = 0 ,041 s 1 k 2 =

1

0 ,027 s 1 k τ 1 = 24 s τ 2 = 37 s